THE VOCABULARY UNDERSTANDING OF READING TEXT IN HOSANNAH BATAM SCHOOL: HOSANNAH BATAM SCHOOL Frangky Silitonga Universitas Putera Batam frangkyka@gmail.com - frangky Silitonga (Universitas Putera Batam, 2015)
Research carried out Team Lecturer English Language and Martial Arts University Putera Batam in grade 7th Junior HOSSANAH Bengkong Batam towards mastery Vocabulary affect the ability of students to teaching Reading Comprehension, shows that the mastery of English vocabulary is directly proportional to the ability of students to read English language students. Students who have a high vocabulary, higher the ability to read English. The same thing happens on a low student mastery of vocabulary, ability to read English also lower